Agro-pesticides: A manual for staff of plant protection services and pesticide distributing companies, for instructors of retailers and professional applicators, and for students of crop production and protection sciences - Oudejans, Jan H (ESCAP, 1991)
In this book, great progress has been made in the development of methods of integrated pest management, particularly for rice, cotton and estate crops. Much attention is being drawn to the need for the rational and safe management of pesticides at the national and international level. It is recognized, however, that a more rational use of pesticides and large scale application of the integrated pest control concept can be achieved only through the training of farmers and all other people professionally engaged in pesticide distribution and application. To this end, this book provides practical and comprehensive information of crop production and crop protection sciences